2013
DOI: 10.4103/2230-8210.111642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autonomic functions in subclinical hypothyroid and hypothyroid patients

Abstract: Background:Autonomic dysfunction may contribute to cardiovascular morbidity in subclinical hypothyroid patients. It is controversial whether the abnormality exists in sympathetic or the parasympathetic function. It is also not known whether the severity of autonomic dysfunction is related to the degree of thyroid deficiency.Design of Study:Prospective case control.Materials and Methods:Autonomic functions based on heart rate (HR) and blood pressure (BP) responses to various maneuvers were evaluated and scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Çelik et al proved that HRV and heart rate (HR) turbulence was reduced in the patient group, and the cardiac autonomic functions did not improve effectively with levothyroxine treatment (7,19). In a previous study by Mahajan et al, it was also demonstrated that autonomic dysfunction may be seen in both subclinical and frank hypothyroidism (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çelik et al proved that HRV and heart rate (HR) turbulence was reduced in the patient group, and the cardiac autonomic functions did not improve effectively with levothyroxine treatment (7,19). In a previous study by Mahajan et al, it was also demonstrated that autonomic dysfunction may be seen in both subclinical and frank hypothyroidism (5).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SH varies between 1% and 10% and increases with age (4). Hypothyroidism is associated with various cardiac pathologies, including impaired cardiac contractility, decreased cardiac output, increased systemic vascular resistance and cardiac electrical abnormalities (5). Electrocardiographic changes, including bradycardia, low voltage and varying degrees of heart block are commonly observed in hypothyroid patients.…”
Section: Introductionmentioning
confidence: 99%
“…The previous study done by Mahajan et al . [ 8 ] also suggested that autonomic dysfunction may be seen in both subclinical and frank hypothyroidisms. [ 8 ] Inukai et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] also suggested that autonomic dysfunction may be seen in both subclinical and frank hypothyroidisms. [ 8 ] Inukai et al . showed that hypothyroidism is associated with increased sympathetic input to the heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation